2018
DOI: 10.1515/iss-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related sclerosing cholangitis mimicking hilar cholangiocarcinoma (Klatskin tumor): a case report of a challenging disease and review of the literature

Abstract: Background:Even though IgG4-related disease has gained increased attention worldwide, the diagnosis remains challenging. IgG4-related sclerosing cholangitis (IgG4-SC) is not well described in the western hemisphere and may mimic cholangiocarcinoma (CC), especially when occurring without other symptoms such as, e.g. concurrent pancreatitis or retroperitoneal fibrosis. We present a case to add further information to the diagnosis and treatment of this challenging disease.Case report:A 60-year-old male patient pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Some reports have described IgG4-SC cases associated with normal or only mildly elevated IgG4 serum levels that were misdiagnosed as cholangiocarcinoma, leading to an unnecessary partial hepatectomy [14, 15]. In our case, the patient was diagnosed with cholangiocarcinoma in 2018.…”
Section: Discussionmentioning
confidence: 68%
“…Some reports have described IgG4-SC cases associated with normal or only mildly elevated IgG4 serum levels that were misdiagnosed as cholangiocarcinoma, leading to an unnecessary partial hepatectomy [14, 15]. In our case, the patient was diagnosed with cholangiocarcinoma in 2018.…”
Section: Discussionmentioning
confidence: 68%
“…Additional case reports [35][36][37][38] about IgG4-SC mimicking cholangiocarcinoma also demonstrated jaundice as the most prevalent initial presentation.…”
Section: Response To Steroid Therapymentioning
confidence: 99%
“…In regard to patients' demographic characteristics, most reported studies [15,[28][29][30][31][32][33][34][35][36][37][38] showed that IgG4-SC, as well as cholangiocarcinoma, affects middle aged to elderly patients (50 -82 years old), and are more common in males than in females.…”
Section: Response To Steroid Therapymentioning
confidence: 99%